Les pongos et les jockos sont-ils des animaux ou des hommes ? L’épreuve de l’incertitude, de Rousseau aux singes parlants - Chris Herzfeld (Revue de Primatologie)
Like the wild children, the anthropoid primates are included in the great anthropological debates of the Eighteenth Century. We ponder upon their status. Rousseau refuses to divide the gap between great apes and the human kind, while others, scientists or philosophers, attempt to widen the gap, rejecting the anthropomorphs in the category of the beast. The chosen criteria of demarcation (language, reason, bipedalism, tool use, emotions, etc.) are greatly relativized as the study of great apes progresses. The apes bring out the ideological dimension of the dualist thought (which radically separate humans and animals), while designating its limits and aporias.